Cause analysis and damage mechanism of explosive destruction with case investigation involving LPG tank trailer. (March 2022) - Wang, Kan; Hu, Qianqian; Qian, Xinming; Li, Mingzhi; Shi, Tingting
Highlights: Investigation elucidates sequencing events in LPG tank trailer failure during transportation. Time-dependent dispersion process is taken into account of evidence for accident causation. Dense structures enhance shock wave initiation and propagation modes. 3D numerical methodology for hazard-specific parameters and predicted damage. Abstract: Identifying causations and failure analysis at the onset holds a key to ensure LPG (liquefied petroleum gas) tank trailer transport safety state and prevent similar failures. Current study presents an unexpected accident by LPG tank trailer, which triggered a massive LPG dispersion and destructive explosion. After the post-accidental scene reconstruction by computational approach, the occurrence of pressurized tank burst and continuous dispersion were detected as an active failure analysis. Macroscopic investigation of the explosion phenomenon involving LPG tank trailer suggested that the causation was responsible for vapor cloud explosion. Hazardous parameters regarding the LPG release, dispersion, explosion shock wave and thermal radiation were represented to identify the mechanisms of potential damages by obtaining at multi-directional area. The visual graphics of flammable gaseous mixtures dispersion showed that the ambient factors imposed great influence on explosive energy reserve in different areas, which were not in accordance with the actual accident scene. The results revealed that the reflected and disturbed effects significantly increased the shock wave, causing more severe structural damage with dense obstacles and elevated flame. A large amount of released gaseous mixtures accumulated, resulting in much higher thermal intensity formed by fireball. This study proposed a failure analysis and classifications of LPG tank trailer accident by explosive destruction integrated with damage mechanism, which contributes to improve the hazard identifications and emergency response under LPG transportation accident sequences.